PENGARUH PENDIDIKAN GRATIS TERHADAP MOTIVASI BELAJAR SISWA SMP KELAS VIII DI KECAMATAN SIMPANG HILIR - Safitri, Ana; Aminuyati, Aminuyati; Khosmas, F. Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed  to determine the effect of free education on motivation to learn in SMP 1, SMP 4 and SMP 9 Kecamatan Simpang Hilir, North Kayong. Data analysis of this study wus simple linear regression analysis, Classical Assumption Test, and hypothesis. This study was conducted based on survey locations in SMP 1, SMP 4 and SMP 9 Simpang Hilir, North Kayong, respondents drawn from the three schools in this study were as many as 69 respondents or students which is collected by using survey method as sample of students of SMP 1 SMP 4 and SMP 9 Simpang Hilir, North Kayong. Data were collected using a questionnaire. The results of the study indicated that free education has significantly influence the motivation to learn. The result of a simple linear regression which has been done obtained regression equation that can be written Y= a + bX or 27,550 + 1,120X coefficient of determination R2 = 0,562 means of 56,2% can be explained by looking on explanatory variable (independent variable) which has been revealed in the model, and 43,8% Influenced by other variables outside this regression model.  Keywords: Free Education, Learning Motivation